The role of responsible leadership in determining the triple-bottom-line performance of the Indonesian tourist industry - Bambang Mantikei; Usup Riassy Christa; Lelo Sintani; Danes Jaya Negara; Meitiana (Contemporary Economics, 2020)
Responsible leadership plays an important role in enhancing innovation to boost up the Triple-Bottom-Line (TBL) performance of the industry. The purpose of the study was to measure the effect of responsible leadership on TBL which includes the social, financial and environmental performance of the Thai tourist industry along with the mediating effect of innovation. The study implemented a cross-sectional design and quantitative research. The employees of the Indonesian tourist sector were the population of the study. Sample size was 250. Simple random technique was used to collect the data. The findings of the study show that responsible leadership prefers to develop good relation among various stakeholders ensure openness and corporation which encourage the employees to stay innovative. Such positivity makes multi-dimensional benefits available to the organization. Moreover, in the presence of responsible leadership, firms are able to achieve higher levels of financial, social and environmental performance. Likewise, responsible leadership engages the employees in innovative activities which ultimately positively affect the TBL performance. From the managerial perspective, this study suggests that having responsible leadership enhances companies' social, environmental and financial performance. Based on this argument, companies should ensure the practices of responsible leadership to keep the employees motivated, innovative and constructive. Moreover, firms need to develop various training programs to develop responsible attitude among managers.
Keywords: L83; O32; 330; Responsible leadership; innovation; social performance; financial performance; environmental performance